Internet banking adoption : information content richness, convenience and computer self-efficacy - Ramlah Hussein, *; Bibi Saidah Pathan (2011)
The purpose of this research study is to examine factors influencing the adoption of Internet Banking among staff in a public university in Malaysia. We investigated three factors that we believed to influence internet banking adoption. A research model was developed to show the relationship between the factors investigated. We used the quantitative method by distributing survey questionnaire to the participants. Ninety seven usable questionnaires were gathered for analysis. The findings indicated that the there are significant relationship between the three factors towards internet banking adoption.